Changing the Fe concentration in the (Ga,Sc,Fe)2O3 spin glass - Strong, Denver; Lee, Sean; Ni, Danrui; Cava, R. J. (Journal of materials science, 2024)
We report the characterization of (GaSc) 2-x Fe x O 3 . The composition range where the multinary metal oxide is stable, as well as nonlinear trends in the lattice parameters are described. Select compositions of GaSc 1-y Fe y O 3 are included to compare trends. Fe shows an enhanced solubility when replacing Sc rather than Ga. Field- and temperature-dependent magnetic data are included, and linear trends in the magnetic frustration are discussed alongside a brief comparison to the magnetic properties of GaSc 1-y Fe y O 3 . The field-dependent properties, as well as anomalies in the hysteresis loops and relaxation of the remnant magnetization are discussed, as well as indications that long-range order may be present in dilute Fe samples.